ANALISIS ALTMAN (Z-SCORE) UNTUK MENILAI FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Masno Marjohan; Cakra Wicaksono; Nur Alim Yuliyanto; Tanri Rekatami (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to determine the possibility of bankruptcy of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022 using Altman (z-score) analysis. The sample was selected using the purposive sampling method. A total of 9 (nine) pharmaceutical companies were selected based on the criteria of being listed on the Indonesia Stock Exchange (BEI), financial reports published consecutively from 2018-2022, and pharmaceutical sub-sector companies that published share prices during 2018-2022. The type of data used in this research is secondary data originating from the site www.idx.co.id. The research results show that the Altman Z-Score model can be implemented in detecting possible financial distress in pharmaceutical companies. As many as 3 (three) of the 9 (nine) sample companies had the lowest Z-Score scores and experienced financial pressure. For 5 (five) years the company is in the gray zone. This certainly shows an initial signal of uncertainty or increased financial risk, but does not mean that the company will go bankrupt. This is a warning that the company must take steps to improve its financial situation and risk management until the company is declared a healthy company.